Degradation analysis of crystalline silicon photovoltaic modules exposed over 30 years in hot-humid climate in China. (August 2018) - Han, Huili; Dong, Xian; Li, Bingzhi; Yan, Huan; Verlinden, Pierre J.; Liu, Jiangfeng; Huang, Jiapei; Liang, Zongcun; Shen, Hui
Highlights: The total power degradation was only 6.53% after 28 years compared to the nameplate value of the modules. The main visually observed defects, after the first 22 years of operation on sun, are yellowing of the EVA, cracks of back-sheet and cracks in cells and corrosion of the metallic fingers or interconnects. The increase of the Yellow Index of the EVA directly results in optical loss, which is believed to be the main cause of the decline of the short-circuit current. Abstract: The main object of this paper is to present the analyze of the degradation mechanism of the electrical properties and polymeric materials for a batch of crystalline-silicon photovoltaic modules, which were installed in the hot-humid region in the south of China for 30 years. Although significant degradation of polymers (EVA and back-sheet) is observed, the average power output is only 6.53% below the name plate of the modules after 30 years in the field. The analysis of electrical performance indicated that the decline of short-circuit current (Isc ) is, in this case, the main cause of power degradation. The degradation of polymeric materials, first observed through visual inspection followed by several analytical methods, such as XPS, optical measurements, or measurement of the degree of crosslinking and mechanical properties, is characterized by a high degree of yellowing of the Ethylene Vinyl Acetate(EVA) and cracks of the back-sheet. In addition, some corrosion of Ag grid is also observed. The high water vapor transmission rate (WVTR) of back-sheet, and the presence of cracks, accelerated the corrosion of metal, but it does not directly result in a decrease of the power output, and no obvious degradation of the filling factor is observed. The increase of the Yellow Index of the EVA directly results in optical loss, which is believed to be the main cause of the decline of the short-circuit current. The loss in short-circuit current caused by EVA discoloration is 12.6% in average, which agrees well with that of electrical performance analysis. Failure cause analysis reveals that there is no direct relationship between the power degradation and the degradation behavior of packaging materials except EVA discoloration.